The Identifikasi dan Prevalensi Endoparasit Pada Feses Sapi Di Kecamatan Setia Janji Kabupaten Asahan - Sirait, Isnawati; Syukriah, Syukriah; Tambunan, Efrida Pima Sari (Universitas Cokroaminoto Palopo, 2024)
Animal health is an absolute requirement to produce optimum productivity. One of the problems faced by cattle farmers is endoparasite attacks that can cause cows to become thin, have no appetite, and lower selling prices. This study aims to determine the types of worm and protozoa endoparasites, the degree of infection, the prevalence and intensity of endoparasitic attacks on cow feces that are raised extensively and intensively in Setia Janji District, Asahan Regency. The methods used for the identification of the type of endoparasite are sedimentation and flotation. While the method used for the calculation of eggs / oocysts per gram of feces uses Mc. Master. From 60 fecal samples examined, 12 species of worms were found, namely Paramphistomum sp., Fasciola sp., Dicrocoelium sp., Oesophagostomum sp., Trichostrongylus sp., Capillaria sp., Haemonchus sp., Cooperia sp., Ascaris sp., Bunostomum sp., Trichuris sp., Strongyloides sp., and 2 protozoa namely Buxtonella sp., and Eimeria sp.